THE INFLUENCE OF PRODUCT QUALITY AND PROMOTION ON THE PURCHASE DECISION OF ORNAMENTAL FISH AT MALIGE AQUARIUM STORE IN BAUBAU CITY - Hasni; Pardana, Deki; Katjina, Husnah; Daholu, Ahmad; Rusdin; Salsabiyla, Fannisa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the effect of product quality and promotion on consumer purchase decisions at Malige Aquarium Store in Baubau City. The research uses a quantitative method with a survey approach involving 97 respondents selected from a population of 3,115 consumers. Data were collected through observation, questionnaires, and documentation, and analyzed using multiple linear regression. The results show that product quality has a significant effect on purchase decisions, indicating that the physical condition and appearance of ornamental fish play an important role in consumer preferences. Promotion also has a significant effect, which means that marketing communication and information delivery can increase consumer interest. The simultaneous test confirms that product quality and promotion together influence purchase decisions. The coefficient of determination shows that 25.3 percent of the variation in purchase decisions is explained by both variables, while the remaining 74.7 percent is influenced by other factors not included in this study. The findings highlight the need for improving fish quality and strengthening promotional strategies to support consumer buying behavior